2009
DOI: 10.1189/jlb.0709520
|View full text |Cite
|
Sign up to set email alerts
|

A GMCSF-neuroantigen fusion protein is a potent tolerogen in experimental autoimmune encephalomyelitis (EAE) that is associated with efficient targeting of neuroantigen to APC

Abstract: Cytokine-NAg fusion proteins represent an emerging platform for specific targeting of self-antigen to particular APC subsets as a means to achieve antigen-specific immunological tolerance. This study focused on cytokine-NAg fusion proteins that targeted NAg to myeloid APC. Fusion proteins contained GM-CSF or the soluble extracellular domain of M-CSF as the N-terminal domain and the encephalitogenic 69-87 peptide of MBP as the C-terminal domain. GMCSF-NAg and MCSF-NAg fusion proteins were approximately 1000-fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(63 citation statements)
references
References 78 publications
(72 reference statements)
1
62
0
Order By: Relevance
“…Previous studies discounted the possibility that administration of GMCSF-MOG in saline elicited anti-GM-CSF antibodies(14). Also, previous studies (1416) showed that treatment with GM-CSF alone or with noncovalently linked NAg lacked tolerogenic activity but nonetheless had the same theoretical potential as GMCSF-NAg to generate anti-GM-CSF antibodies. The use of B cell-deficient mice provided a definitive assessment of this issue.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies discounted the possibility that administration of GMCSF-MOG in saline elicited anti-GM-CSF antibodies(14). Also, previous studies (1416) showed that treatment with GM-CSF alone or with noncovalently linked NAg lacked tolerogenic activity but nonetheless had the same theoretical potential as GMCSF-NAg to generate anti-GM-CSF antibodies. The use of B cell-deficient mice provided a definitive assessment of this issue.…”
Section: Resultsmentioning
confidence: 99%
“…GMCSF-NAg fusion proteins comprised of GM-CSF and dominant myelin epitopes of MBP, MOG, and PLP were potent NAg-specific tolerogens in rat and mouse models of EAE(14-16). GMCSF-NAg proteins were tolerogenic vaccines when administration was completed before immunization and were effective interventions when GMCSF-NAg treatment was initiated after onset of EAE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with these mucosal sources, GM-CSF mRNA is increased in the airways of human asthmatics (Chung and Barnes, 1999) where it promotes maturation, activation, and growth of monocytes and DCs, resulting in increased antigen presentation and activation of antigen-specific B and T cells (Chung and Barnes, 1999). GM-CSF also contributes to T H 17-induced inflammatory responses (Ganesh et al, 2009;Blanchfield and Mannie, 2010;Hamilton and Anderson, 2004;Ritz et al, 2002).…”
Section: Granulocyte-macrophage Colony Stimulating Factormentioning
confidence: 70%
“…It is unclear how this could induce Ag-specific tolerance, but the investigators speculated that APCs may be involved, because the IL-16/MBP fusion was effective at having APCs present MBP through MHC class II to Rsl.11 T cells (11). Blanchfield and Mannie (14) further explored how cytokines could be fused to more effectively deliver MBP to APCs by combining it with GM-CSF, finding that this fusion was also capable of significantly reducing the severity of EAE in rats. The investigators believed that the GM-CSF moiety acts as a delivery vehicle for MBP, because the two need to be linked for the fusion to suppress EAE.…”
mentioning
confidence: 99%